Insertion of a transposon‐like sequence in the 5′‐flanking region of the YUCCA gene causes the stony hard phenotype. (28th September 2018) - Tatsuki, Miho; Soeno, Kazuo; Shimada, Yukihisa; Sawamura, Yutaka; Suesada, Yuko; Yaegaki, Hideaki; Sato, Akiko; Kakei, Yusuke; Nakamura, Ayako; Bai, Songling; Moriguchi, Takaya; Nakajima, Naoko
Summary: Melting‐flesh peaches produce large amounts of ethylene, resulting in rapid fruit softening at the late‐ripening stage. In contrast, stony hard peaches do not soften and produce little ethylene. The indole‐3‐acetic acid (IAA) level in stony hard peaches is low at the late‐ripening stage, resulting in low ethylene production and inhibition of fruit softening. To elucidate the mechanism of low IAA concentration in stony hard peaches, endogenous levels of IAA and IAA intermediates or metabolites were analysed by ultra‐performance liquid chromatography‐tandem mass spectrometry. Although the IAA level was low, the indole‐3‐pyruvic acid (IPyA) level was high in stony hard peaches at the ripening stage. These results indicate that YUCCA activity is reduced in ripening stony hard peaches. The expression of one of the YUCCA isogenes in peach, PpYUC11, was suppressed in ripening stony hard peaches. Furthermore, an insertion of a transposon‐like sequence was found upstream of the PpYUC11 gene in the 5′‐flanking region. Analyses of the segregation ratio of the stony hard phenotype and genotype in F1 progenies indicated that the transposon‐inserted allele of PpYUC11, hd‐t, correlated with the stony hard phenotype. On the basis of the above findings, we propose that the IPyA pathway (YUCCA pathway) is the main auxin biosynthetic pathway in ripening peaches of 'Akatsuki' and 'Manami' cultivars. Because IAA is not supplied from storage forms, IAA de novo synthesis via the IPyA pathway (YUCCA pathway) in mesocarp tissues is responsible for auxin generation to support fruit softening, and its disruption can lead to the stony hard phenotype. Significance Statement: We found that the indole‐3‐pyruvic acid pathway is the main auxin biosynthetic pathway in peaches, and it is disrupted in the stony hard cultivar to inhibit fruit softening at the ripening stage. Expression of PpYUCCA11, encoding an enzyme critical to auxin biosynthesis, was suppressed in ripening stony hard peaches due to insertion of a transposon in the 5′ upstream regulatory region of the PpYUC11 gene.